Analysis of Net Enumeration Rate of Senior High School Using Fixed-Effect Clustered-Robust Standard Error Model: Analisis Angka Partisipasi Murni Sekolah Menengah Menggunakan Model Fixed-Effect Clustered Robust Standard Error - Leonita Amara Husna Metanda; Siskarossa Ika Oktora (Indonesian Journal of Statistics and Applications, 2022)
The Net Enumeration Rate (NER) of senior high school (SHS) in Indonesia in 2017-2019 always be the lowest than the other education levels and cannot fulfill the target of the 2014-2019 National Medium-Term Development Plan (RPJMN). This study aims to analyze the determinants of NER of SHS in Indonesia 2017-2019 using the panel data regression method. The independent variables include child labor, child marriage, Smart Indonesia Program (PIP), repeat rates, and poverty. The NER of SHS is the dependent variable. Based on the modeling, heteroscedasticity and autocorrelation problems are found. The fixed-effect clustered-robust standard error method is used to solve these problems. The results show that the NER of SHS increased every year, and poverty decreased every year. Meanwhile, other variables fluctuate during 2017-2019. Furthermore, it is found that child labor and poverty significantly affect the NER of SHS in Indonesia. Meanwhile, child marriage, PIP, and repeat rates have no significant effect. This study can be used by local government to implement more effective policies based on the factor that do have significant effects on NER of SHS in Indonesia in 2017-2019.